Guilt and Burnout in Medical Students. Issue 1 (20th January 2022) - Greenmyer, Jacob R.; Montgomery, Michelle; Hosford, Charles; Burd, Michael; Miller, Vanessa; Storandt, Michael H.; Lakpa, Koffi L.; Tiongson, Christopher
Abstract: Theory: Burnout is prevalent among medical students and is correlated with negative feelings, behaviors, and outcomes. Empathy is a desired trait for medical students that has been correlated with reduced burnout. The concept of guilt is closely related to concern about the well-being of others; therefore, feelings of guilt may be associated with empathy. Excessive guilt poses an increased risk for internalized distress, symptoms such as anhedonia, and may be related to burnout. The relationship between pathogenic guilt and burnout in medical students is unknown. Hypothesis: We hypothesize that pathogenic guilt is present and related to both burnout and empathy in medical students. Methods: We conducted a cross-sectional survey study of all students in one medical school. Data were collected in February 2020. The Oldenburg Burnout Inventory (OBLI), Toronto Empathy Questionnaire (TEQ), and Interpersonal Guilt Questionaire-67 (IGQ-67) were used. A modified version of IGQ-67 was used to measure four subscales of pathogenic guilt: survival guilt, separation guilt, omnipotence guilt, and self-hate guilt. Data analyses for this study including screening, evaluation of assumptions, descriptive statistics, reliabilities, one-way ANOVA, and correlation coefficients, were conducted using SPSS version 26. Results: Of 300, 168 (56.0%) students participated in the study. Survival, omnipotence, and self-hate classes of pathogenic guilt were positively correlated with burnout. Empathy was correlated with two classes of pathogenic guilt: survival and omnipotence. Empathy was inversely related to burnout (disengagement). Conclusions: Pathogenic guilt may be a contributor to burnout in medical students. Guilt should be a target of prevention and treatment in burnout in medical students. Supplemental data for this article is available online at https://doi.org/10.1080/10401334.2021.1891544 .